Hybrid estimator for chemical product composition - Arshad Ahmad, 1963-; Lim, Wan Piang; Chen, Wah Sit; Artificial Intelligence Applications in Industry (2003 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2003)
50